«Tiziano?», «Correggio?». Due expertises di Ludwig Baldass e Roberto Longhi nell’archivio di Antonio Morassi - Giulio Zavatta (Ricerche di S/Confine, 2017)
The Photo Archive Antonio Morassi (Ca' Foscari University of Venice) contains a unique file with photographs and expertises on two paintings attributed to Titian and Correggio. This paper aims to investigate the role played by the two art historians Ludwig Baldass and Roberto Longhi in this "affair", which represents an evocative case study for the history of Italian art market after the Second World War, and for the critical debate over Correggio and his legacy.